2016
DOI: 10.3389/fnhum.2016.00572
|View full text |Cite
|
Sign up to set email alerts
|

Noise Improves Visual Motion Discrimination via a Stochastic Resonance-Like Phenomenon

Abstract: The stochastic resonance (SR) is a phenomenon in which adding a moderate amount of noise can improve the signal-to-noise ratio and performance of non-linear systems. SR occurs in all sensory modalities including the visual system in which noise can enhance contrast detection sensitivity and the perception of ambiguous figures embedded in static scenes. Here, we explored how adding background white pixel-noise to a random dot motion (RDM) stimulus produced changes in visual motion discrimination in healthy huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 69 publications
5
29
0
Order By: Relevance
“…Our results are in line with recent work that employed a similar task to show that decision-making is sensitive to the addition of noise to visual motion stimuli [41]. Critically, our findings extend these results by demonstrating that a stochastic resonance effect can be induced in a decision-making task when noise is directly applied to the visual cortex with tRNS [42, 43].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in line with recent work that employed a similar task to show that decision-making is sensitive to the addition of noise to visual motion stimuli [41]. Critically, our findings extend these results by demonstrating that a stochastic resonance effect can be induced in a decision-making task when noise is directly applied to the visual cortex with tRNS [42, 43].…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, the authors found that the injection of different hf-tRNS intensities modulated detection accuracy of subthreshold stationary stimuli in a stochastic resonance manner. There is also psychophysical evidence that the addition of external visual noise can improve performance in a motion direction discrimination task [68]. The effects of hf-tRNS on the direction discrimination tasks used in our study can be explained within the stochastic resonance framework; that is, the neural noise induced by hf-tRNS could increase the signalling of neurons to a specific motion direction (i.e., sampling), and consequently improve the performance.…”
Section: Discussionmentioning
confidence: 66%
“…The vWM task had three experimental conditions, with different levels of visual load and configuration. Although adding visual loading and configuration in the form as a static field, or distortion of the whole image is a common strategy [54][55][56][57], we opted to instead use the outline of a larger polygon as our visual item manipulation. The rationale for this decision was as follows; the loading or configuration alteration included is rather conservative, as we wanted to avoid interfering too much with perceptual processes (e.g., decreasing stimuli identification [58]), this was also the rationale for adding the geometric stimulus as background, rather than foreground.…”
Section: Experimental Taskmentioning
confidence: 99%